The Socio-Political Identity of Eu Countries: A Systematization of Security Theories (Eurasian Journal of History, Geography and Economics, 2023)
The article examines the development and specificity of the perception of European identity through the prism of security theories. It demonstrates how the European identity is created by the method "from the opposite", that is, on the basis of the production and exclusion of "foreign" identities. It examines how the perception of threats to European identity is related to their vision of Europe, formulated in various directions, for example, cultural heritage, socio-economic order and supranational governance versus intergovernmentalism. It is argued that the politico-social identification of security is a powerful factor contributing to the regular maintenance of a strategy to combat threats to the identity of a cohesive Europe. It is concluded that the experience of constructing a European identity is vulnerable, since the lack of a clear strategy for foreign and security policy, with the creation of an image of an external “other” or “foreign”, will entail a search for “unrecognized identities” within the EU, which is fraught with confrontation between the association and nations .